2018
DOI: 10.1111/nyas.13681
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy of esophageal squamous cell carcinoma: the NRF2 signaling pathway as target

Abstract: Esophageal squamous cell carcinoma (ESCC) is a deadly disease that requires extensive research. Here, we review the current understanding of the functions of the nuclear factor erythroid-derived 2-like 2 (NRF2) signaling pathway in the esophagus. Genomic data suggest that gene mutations and several other mechanisms result in NRF2 hyperactivation in human ESCC. As a consequence, NRF2 ESCC is more resistant to chemoradiotherapy and associated with poorer survival than NRF2 ESCC. Mechanistically, we believe NRF2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 119 publications
(249 reference statements)
0
27
0
Order By: Relevance
“…NRF2 mutations are mostly located in the DLG and ETGE motifs (KEAP1-binding domain) and the DNA-binding domain, whereas KEAP1 mutations tend to be scattered across the whole gene. NRF2 mutations and KEAP1 mutations tend to be mutually exclusive (3,4).…”
Section: Summary Hyperactive Nrf2 Causes Metabolic Reprogramming In mentioning
confidence: 99%
See 1 more Smart Citation
“…NRF2 mutations are mostly located in the DLG and ETGE motifs (KEAP1-binding domain) and the DNA-binding domain, whereas KEAP1 mutations tend to be scattered across the whole gene. NRF2 mutations and KEAP1 mutations tend to be mutually exclusive (3,4).…”
Section: Summary Hyperactive Nrf2 Causes Metabolic Reprogramming In mentioning
confidence: 99%
“…NRF2 mutations are mostly located in the DLG and ETGE motifs (KEAP1-binding domain) and the DNA-binding domain, whereas KEAP1 mutations tend to be scattered across the whole gene. NRF2 mutations and KEAP1 mutations tend to be mutually exclusive (3,4).As a major cellular defense mechanism, the NRF2 signaling pathway is known to regulate expression of enzymes involved in detoxification and anti-oxidative stress response. NRF2 forms heterodimers with small MAF proteins and binds to the antioxidant-response elements of target genes when cells are…”
mentioning
confidence: 99%
“…Kawasaki et al reported the possibility of the conversion of non-responder patients to responders by Nrf2 knockdown before subjecting patients with ESCC with high-Nrf2 expression to CRT, which may lead to a more favorable prognosis [29]. In contrast, targeting the transcription factor Nrf2 was considered signi cantly challenging in clinical settings [43]. To include curative resection as a viable treatment option for ESCC, surgical resection without NAC or NACRT might be a potential treatment strategy for patients with ESCC who exhibit high Nrf2, TXNRD1, and HO-1 expression, considering the highly aggressive malignant tendencies of tumors and the probable ineffectiveness of neoadjuvant therapy [17,18,24,25,44].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, inhibition of Nrf2 signaling enhances apoptosis in response to oxidative insults [15]. There are many studies showing elevated expression of Nrf2 in various types of tumors such as head and neck [16], gastric [17], non-small cell lung [18], esophageal squamous cell carcinoma [19], breast [20], gallbladder [21] and ovarian [22] cancer. Upon oxidative stress, Nrf2 signaling is activated and protects tumor cells from cell death by upregulating ROS scavenging enzymes that counterbalance 0production [23].…”
Section: Introductionmentioning
confidence: 99%